The Competency of Social Worker as a Leader in Managing the Rumah Zakat Social Service Institution and in the Success of the “Kado Cinta Anak Disabilitas” Program - Tahrizi Fathul Aliim; Soni Akhmad Nulhaqim; Maulana Irfan (Jurnal Manajemen Pelayanan Publik, 2023)
This research aims to descriptively investigate the competencies of leaders and their impact within the Department of Research and Program Development (RPD). The focus of the study is on the dual role of leaders as coordinators and administrators of social work, addressing barriers in the institution's administrative processes often hindered by a lack of human resources. The research problem highlights the need for social workers' competence as coordinators and administrators who understand the goals, policies, resources, administration, services, management functions, and evaluation. The study identifies gaps related to the dual role of social work leaders and emphasizes the lack of understanding and research on the urgency of this role. The research focuses on the impact of insufficient human resources on the administrative services of the institution, with an emphasis on a deep understanding of the competencies of social workers in their dual role. The results of the research indicate that leaders in the RPD Department have competencies through knowledge, attitudes, and actions, particularly in accompanying the design and implementation process of the “Kado Cinta Anak Disabilitas" program. The importance of understanding how leader competencies affect the quality of services and the work environment that supports employee well-being and mental health needs to be emphasized for a significant contribution to the development of this field.